Procedure for the Screening of Eggs and Egg Products to Detect Oxolonic Acid, Ciprofloxacin, Enrofloxacin, and Sarafloxacin Using Micellar Liquid Chromatography - Juan Peris-Vicente; Daniel García-Ferrer; Pooja Mishra; Jaume Albiol-Chiva; Abhilasha Durgbanshi; Samuel Carda-Broch; Devasish Bose; Josep Esteve-Romero (MDPI AG, 2019)
A method based on micellar liquid chromatography was developed to determine oxolinic acid, ciprofloxacin, enrofloxacin, and sarafloxacin in eggs and egg products. The antimicrobial drugs were obtained in a micellar solution which was directly injected. The analytes were resolved using a C18 column and a mobile phase of 0.05 M sodium dodecyl sulfate-7.5% 1-propanol-0.5% triethylamine, buffered at pH 3 with phosphate salt, running under the isocratic mode. The signal was monitored by fluorescence. Validation was successfully performed according to the EU Commission Decision 2002/657/EC in terms of specificity, calibration range (LOQ to 1 mg/kg), linearity (R2 > 0.9991), limit of detection and decision limit (0.01-0.05 mg/kg), limit of quantification (0.025-0.150 mg/kg), detection capability (<0.4 times decision limit), trueness (−14.2% to +9.8%), precision (<14.0%), robustness, and stability. The procedure was environmentally friendly, safe, easy-to-conduct, inexpensive, and had a high sample throughput, thus it is useful for routine analysis as a screening method in a laboratory for food residue control.